Double-stranded RNA antiviral signature in early multiple sclerosis - Gouzouasis, Vasileios; Sarrigeorgiou, Ioannis; Tsifintaris, Margaritis; Markoglou, Nikos; Georgopoulou, Urania; Lymberi, Peggy; Anagnostouli, Maria; Probert, Lesley; Giannakakis, Antonis (Frontiers in Microbiology, 2025)
IntroductionViruses, particularly Epstein–Barr virus (EBV), are strongly implicated in multiple sclerosis (MS) pathogenesis, yet reliable biomarkers of active viral replication remain limited. Double-stranded RNA (dsRNA) represents a hallmark of viral replication and may serve as a measurable indicator of viral infection.MethodsWe developed a sandwich ELISA to quantify dsRNA levels in matched plasma and cerebrospinal fluid (CSF) samples from 70 treatment-naïve MS patients at first clinical onset and in plasma from 26 sex- and age-matched healthy controls. We additionally assessed plasma and CSF antiviral cytokine concentrations and designed an indirect ELISA to measure anti-dsRNA antibody levels using poly(I:C) as the target antigen.ResultsPlasma dsRNA levels were significantly elevated in MS patients compared to controls and positively correlated with antiviral cytokines, including GM-CSF, IFN-λ1, IFN-λ2/3, IFN-γ, IFN-α2, and IL-12p70. CSF samples exhibited increased IP-10 and IL-8 levels, and the single patient with detectable CSF dsRNA showed among the highest concentrations of both cytokines. A subset of ten patients (14%) with serological evidence of atypical EBV reactivation (EBNA1 IgG+/IgM+) had higher plasma dsRNA and antiviral cytokine levels than the remaining patients. Anti-dsRNA IgM, but not IgG or IgA, correlated positively with plasma dsRNA in both MS patients and controls, yet anti-dsRNA IgM levels were significantly reduced in MS compared to controls.DiscussionOur findings identify increased plasma viral dsRNA coupled with reduced anti-dsRNA IgM antibody levels as potential biomarkers for a subpopulation of early MS patients and indicate a dysregulated anti-viral immune response.